Role of the Internet and Social Media in Recruitment Practices in Pakistan - Shaikh, Jahan (2013)
Over the past twenty years, the use of the internet has become an integral part of our daily lives. All across the globe, young and old alike are using the internet for various purposes every day. Lately, social networking websites have permeated into our lives, and are now connecting millions of people around the world. Slowly now, these social networking forums are being used for more than just staying in touch with family and friends; they are becoming fully integrated with basic organizational functions such as marketing and recruitment, and are more frequently being used by large corporations to carry out these functions. Researchers have observed a phenomenal increase in the number of organizations and institutions around the world, that have recently started using the internet and social networking for the recruitment of new employees and the advertisement of job openings. The use of online recruitment tools has made the hiring process much easier, faster and more cost effective for these organizations. The aim of this dissertation is to examine the extent to which these online recruitment tools are being used by organizations in a developing country like Pakistan, and the degree of importance given to this method of recruitment by Pakistani human resource professionals. This study takes a qualitative approach, and uses semi-structured interviews to discover the views and opinions of human resource managers in the country. A sample of ten managers were interviewed, all belonging to multinational companies and large local corporations operating within various industries based in the two major Pakistani cities of Lahore and Karachi.